Salvage endoscopic resection as a treatment for locoregional failure or recurrence following chemoradiotherapy or radiotherapy for esophageal cancer - NAKAMURA, RIEKO (Oncol Lett, 2016)
Radiotherapy (RT) or chemoradiotherapy (CRT) is a potentially curative, non-surgical treatment option for esophageal cancer, although the rate of local failure within the esophagus remains relatively high. Salvage esophagectomy is not regarded as a common treatment for esophageal cancer, since it is a high-risk surgery with a relatively high surgical mortality rate. Salvage endoscopic resection (ER) for local failure is used for treatment when esophageal cancer is localized and superficial. To evaluate to usefulness of salvage ER, the present study reviewed the clinicopathological records and follow-up data of 37 patients that underwent salvage ER for esophageal cancer, following initial treatment with RT or CRT. Salvage ER was conducted on a total of 78 lesions observed in the 37 patients. Since a thick epithelium and lack of normal vessels on the surface of the mucosa are characteristics of esophageal mucosa following RT or CRT, almost all the lesions were detected using iodine dyeing, and not by narrow band imaging. The growth rate of the detected lesions was relatively high, and early treatment was required. No particular complications occurred during the endoscopic treatment. A total of 11 patients survived for >5 years subsequent to initial endoscopic treatment. Only 4 patients succumbed to esophageal cancer. In conclusion, the present study demonstrated that salvage ER following CRT or RT for esophageal cancer is a minimally invasive, safe, adaptive and curative method for superficial lesions without distant metastases in patients with esophageal cancer with local failure following CRT or RT.